Analisa Kerentanan Sistem Dengan Menerapkan Open Vulnerability Assessment System Menggunakan Greenbone Vulnerability Management (GVM) - Muh. Ahsan; Dwi Anindyani Rochmah (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2022)
A computer network is a network telecommunication that connects one or more computers to exchange data and information with each other. Such huge benefit will certainly be reduced by the presence of interference that arises in the network, when the network only involves local devices or in other words, is not connected to the internet network then interference may be less calculated. However, when the local network is connected to the internet network, a security system will be something that must be considered. Every system and network will undoubtedly have vulnerabilities and can cause damage to the system and even data to cause losses. Tracing activities and identifying system vulnerabilities are effective ways to minimize the risk of continuous vulnerability, therefore this study aims to conduct network analysis to determine vulnerabilities system by applying the open vulnerability assessment system method using Greenbone Vulnerability Management (GVM) as a platform of network scanning and vulnerability management system. The results are achieved by doing the vulnerability analysis to evaluate the results of vulnerability findings and then categorized according to the level of risk, namely high, medium and low. Conducting a vulnerability assessment will improve information security and avoid bad risks that can cause losses. The results achieved doing the vulnerability assessment activity are to provide an evaluation of the risk of vulnerability found and the impact that can be generated and as a preventive measure to increase security system awareness.